Comparison of the prognosis of primary and progressive muscle-invasive bladder cancer after radical cystectomy: A systematic review and meta-analysis. (April 2018) - Chen, Junru; Zhang, Haoran; Sun, Guangxi; Zhang, Xingming; Zhao, Jinge; Liu, Jiandong; Shen, Pengfei; Shi, Ming; Zeng, Hao
Abstract: Objective: The aim of the study was to systematically review the relevant studies to evaluate the prognosis of primary and progressive muscle-invasive bladder cancer (MIBC) after radical cystectomy (RC) and provide a clue for the timing of RC in patients with progressive MIBC early at the time of high-risk non-muscle-invasive bladder cancer (NMIBC). Material and methods: PubMed, MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials were searched for eligible studies. We extracted hazard ratios (HRs) of overall survival (OS) and cancer-specific survival (CSS) and deaths at 5 and 10 years for each study and performed the meta-analysis using Review Manager 5.3. Results: A total of 11 retrospective studies with 4102 patients were included in the meta-analysis. The pooled analysis suggested a similar CSS (HR: 1.18; 95% CI, 0.74, 1.87; p = 0.50) and OS (HR: 1.15; 95% CI, 0.82, 1.61; p = 0.43) between primary and progressive MIBC patients treated with RC. The results further indicated no significant differences between the two populations in terms of 5-year CSS rate (OR: 1.32; 95% CI, 0.90, 1.95; p = 0.16), 10-year CSS rate (OR: 0.83; 95% CI, 0.37, 1.83; p = 0.64) as well as 5-year OS rate (OR: 1.02; 95% CI, 0.66, 1.56; p = 0.94). Subgroup analysis according to the starting point of follow-up showed similar outcomes. Conclusion: The meta-analysis demonstrates comparable CSS and OS in patients with primary and progressive MIBC following RC. Novel risk stratifications and prospective trials are urgently needed to investigate the prognosis after RC of these two groups of patients, which could finally aid clinician decision making and select patients who would actually benefit from early RC. Highlights: The prognosis after RC of primary and progressive MIBC is comparable. MIBC progress from high-risk NMIBC may have worse survival outcomes. Novel risk stratifications and relevant prospective trials are needed.